2009
DOI: 10.1371/journal.pone.0005561
|View full text |Cite
|
Sign up to set email alerts
|

Is HIV Infection a Risk Factor for Multi-Drug Resistant Tuberculosis? A Systematic Review

Abstract: BackgroundTuberculosis (TB) is an important cause of human suffering and death. Human immunodeficiency virus (HIV), multi-drug resistant TB (MDR-TB), and extensive drug resistant tuberculosis (XDR-TB) have emerged as threats to TB control. The association between MDR-TB and HIV infection has not yet been fully investigated. We conducted a systematic review and meta-analysis to summarize the evidence on the association between HIV infection and MDR-TB.Methods and ResultsOriginal studies providing Mycobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
138
3
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(172 citation statements)
references
References 36 publications
20
138
3
6
Order By: Relevance
“…A systematic review 31 found that several studies have reported a high proportion of resistant cases in patients with tuberculosis co-infected with HIV in specific outbreak settings such as prisons and hospitals, but few studies have systematically compared prevalence of multidrug resistance between HIV-infected and uninfected patients after controlling for other factors. A 2009 systematic review that summarised 32 eligible studies noted a statistically significant association between HIV co-infection and primary but not secondary multidrug resistance, but most of the studies included in the analysis were not adjusted for confounders.…”
Section: Comorbidities As Risk Factors For Mdrmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review 31 found that several studies have reported a high proportion of resistant cases in patients with tuberculosis co-infected with HIV in specific outbreak settings such as prisons and hospitals, but few studies have systematically compared prevalence of multidrug resistance between HIV-infected and uninfected patients after controlling for other factors. A 2009 systematic review that summarised 32 eligible studies noted a statistically significant association between HIV co-infection and primary but not secondary multidrug resistance, but most of the studies included in the analysis were not adjusted for confounders.…”
Section: Comorbidities As Risk Factors For Mdrmentioning
confidence: 99%
“…A 2009 systematic review that summarised 32 eligible studies noted a statistically significant association between HIV co-infection and primary but not secondary multidrug resistance, but most of the studies included in the analysis were not adjusted for confounders. 31 A study in Kazakhstan showed that, although risk factors for HIV and MDR tuberculosis largely overlapped, HIV was not a risk factor for MDR once the socioeconomic risk factors for both diseases had been taken into account. 32 Studies on diabetes as a risk factor for MDR tuberculosis have been similarly heterogeneous.…”
Section: Comorbidities As Risk Factors For Mdrmentioning
confidence: 99%
“…Irrespective of the CD4 cell count and ART therapy, the risk of death in co-infected individuals is twice that of HIV positive patients without TB. 15 While HIV infection speeds up the progression from latent to active TB almost 12-20 times, 1,16 TB bacteria accelerates the progress of HIV infection to full blown AIDS. 17 In 2013, an estimated 1.1/9 million (13%) people who developed TB, were HIV positive.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in co-infected individuals the risk of death is twice that of HIV infected individuals without TB, even when CD4 cell count and antiretroviral therapy are taken into account. [8] Many people are not aware of being infected with tubercle bacillus; the infection thus becomes reactivated by other infections such as the HIV when the body immune system is weakened. People living with HIV or immunosuppressed patients due to drugs seem more vulnerable to tuberculosis (TB) than HIV uninfected persons.…”
Section: Introductionmentioning
confidence: 99%
“…Overall it is considered that the lifetime uncertainty for HIV negative individual of progressing from latent to active TB is about 5-10%, whereas for HIV positive people this same figure is the annual risk. [8] Without proper treatment, an estimated 90 percent of persons living with HIV die within months after contracting tuberculosis. [1] The initiation of highly active antiretroviral therapy (HAART) in persons co-infected with tuberculosis can cause an immune reconstitution inflammatory syndrome with a worsening, in some cases severe worsening, of tuberculosis infection and symptoms.…”
Section: Introductionmentioning
confidence: 99%